SCS-CN MODEL FOR QUANTIFYING SURFACE RUNOFF POTENTIAL IN THE ECOREGION SEGMENTATION OF BANTUL REGENCY - Faridah Nur Isnaini; Alfina Lismadanti; Katyusha Fiore; Lisa Mustafidatul Fauziah; Michelle Ruth Boru Girsang; Muhammad Farhan Athaya; Satrio Budiman; Tuhu Satrio Nugroho; Mohammad Pramono Hadi (Universitas Sebelas Maret (UNS), 2024)
The role of surface air is pivotal within the framework of human livelihoods, necessitating a thorough examination of the potentiality inherent in surface water resources. This study aims to ascertain the estimations of surface runoff potential within Bantul Regency for the year 2020, serving as a watershed area, employing the Soil Conservation Service-Curve Number (SCS-CN) model grounded in ecoregion segmentation. Empirical data pertaining to spatial distribution of rainfall, soil types, and land use are meticulously analyzed to delineate hydrological soil group (HSG) and corresponding curve numbers (CN). The geospatial integration of these datasets is overlaid, facilitating landform mapping. Notably, the CN values are predicated upon three distinct Antecedent moisture conditions (AMC), delineated as AMC I, II, III denoting dry, normal, and wet conditions, respectively. The research findings reveal that surface runoff volume within Bantul Regency is predominantly concentrated within the landform expanse characterized as F2-Qmi, registering at 119,971,277.78 m3 during the rainy season and 376,473 m3 during the dry season. By contrast, the lowest runoff volume is observed in M1-Qa, amounting to 126,811.85 m3 during the rainy season and 0.61 m3 during the dry season. To ensure the availability of potential surface runoff influenced by various ecoregions, it is essential to conduct detailed mapping, implement ecosystem conservation, construct reservoirs in dry areas, and engage communities through education and supportive zoning policies for sustainable water management.